Prediction of Equilibrium Mixing Index and Optimum Mixing Time for Three solid materials in Fluidized Column - Abbas H. Sulaymon (Al-Khwarizmi College of Engineering – University of Baghdad, 2010)
Equilibrium and rate of mixing of free flowing solid materials are found using gas fluidized bed. The solid materials were sand (size 0.7 mm), sugar (size0.7 mm) and 15% cast iron used as a tracer. The fluidizing gas was air with velocity ranged from 0.45-0.65 m/s while the mixing time was up to 10 minutes. The mixing index for each experiment was calculated by averaging the results of 10 samples taken from different radial and axial positions in fluidized QVF column 150 mm ID and 900 mm height.